Perencanaan Manajemen Sumber Daya Manusia di Sekolah (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to determine the construction or concept of human resource management, human resource management functions, and human resource management applications. This research is a qualitative research . The technique used in determining the informants is purposive sampling. Data collection techniques by conducting observations, interviews, and document studies. Furthermore, the data analysis technique of this research uses Miles and Huberman type analysis which divides the analysis including data collection, data reduction, data display and conclusion drawing, verification. Furthermore, this research shows that the application of human resource management at SMP Muhammadiyah 2 Way Jepara, East Lampung is to carry out human resource needs planning, human resource procurement, human resources  achievement evaluation and development.